Sociality sculpts similar patterns of molecular evolution in two independently evolved lineages of eusocial bees - Shell, Wyatt A. (Commun Biol, 2021)
While it is well known that the genome can affect social behavior, recent models posit that social lifestyles can, in turn, influence genome evolution. Here, we perform the most phylogenetically comprehensive comparative analysis of 16 bee genomes to date: incorporating two published and four new carpenter bee genomes (Apidae: Xylocopinae) for a first-ever genomic comparison with a monophyletic clade containing solitary through advanced eusocial taxa. We find that eusocial lineages have undergone more gene family expansions, feature more signatures of positive selection, and have higher counts of taxonomically restricted genes than solitary and weakly social lineages. Transcriptomic data reveal that caste-affiliated genes are deeply-conserved; gene regulatory and functional elements are more closely tied to social phenotype than phylogenetic lineage; and regulatory complexity increases steadily with social complexity. Overall, our study provides robust empirical evidence that social evolution can act as a major and surprisingly consistent driver of macroevolutionary genomic change.